2011
DOI: 10.5005/jp-journals-10011-1121
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Oral Health Indicators in Type 2 Diabetes Mellitus Patients and Controls

Abstract: Introduction: India leads the world with largest number of diabetic subjects earning the dubious distinction of being termed the 'diabetes capital of the world'. Oral manifestations of diabetes mellitus are devastating, these include gingival and periodontal diseases, bone loss, dental caries, alterations in salivary flow and others.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
4
0
2
Order By: Relevance
“…A study compared T1D versus non-DM (DFS T1D = 0.24 ± 0.14; DFS non-DM = 0.28 ± 0.13) [24]. Other 12 studies evaluated T2D compared with a non-DM group [15,18,[25][26][27][28][29][30][31][32][33][34]. Seven of them showed the prevalence of dental caries in T2D and non-DM individuals, but only one of them had a statistically significant higher prevalence of caries in T2D [15, 26-29, 31, 34].…”
Section: Qualitative and Quantitative Results For Each Pecos Questionmentioning
confidence: 99%
“…A study compared T1D versus non-DM (DFS T1D = 0.24 ± 0.14; DFS non-DM = 0.28 ± 0.13) [24]. Other 12 studies evaluated T2D compared with a non-DM group [15,18,[25][26][27][28][29][30][31][32][33][34]. Seven of them showed the prevalence of dental caries in T2D and non-DM individuals, but only one of them had a statistically significant higher prevalence of caries in T2D [15, 26-29, 31, 34].…”
Section: Qualitative and Quantitative Results For Each Pecos Questionmentioning
confidence: 99%
“…An increase in number of lost teeth in diabetic patients with xerostomia might be attributed to tooth mobility due to periodontal diseases and an increase in the incidence of tooth decay in such patients, which is consistent with the results of present study, indicating higher CAL and more lost teeth in patients with xerostomia. Tobacco use in diabetic patients results in poor oral hygiene, increasing DMFT, PLI, GI and PDI and increases the odds of periodontitis [ 25 , 26 ]. This study only showed a relationshipbetween an increase in PLI and tobacco use in diabetic patients and it was not possible to establish a relationship between tobacco use and other oral signs and symptoms due to limited number of diabetic patients who used tobacco.…”
Section: Discussionmentioning
confidence: 99%
“…Pasien DMT2 memiliki nilai rerata OHIS yang lebih buruk daripada pasien non DM. Hasil penelitian ini didukung oleh temuan penelitian Sharma et al 12 yang menunjukkan perbedaan bermakna dari OHIS antara pasien dengan DMT2 dengan kontrol tanpa DM, dan Barrientos et al 13 Perbedaan indeks kebersihan mulut tersebut dapat diakibatkan oleh meningkatknya risiko kebersihan mulut yang lebih buruk pada pasien dengan DM. 14 Terdapat beberapa mekanisme yang berperan dalam hal meningkatnya risiko untuk kebersihan mulut yang lebih buruk pada pasien dengan DMT2.…”
Section: Bahasanunclassified
“…Hal ini dapat disebabkan adanya faktor lain yang memengaruhi kebersihan mulut seperti merokok, kebiasaan maupun cara menyikat gigi, pendidikan, dan status sosioekonomi. Alasan tersebut didukung oleh temuan penelitian Sharma et al 12 yaitu saat analisis perbandingan OHIS antara pasien DMT2 dan non DM dibatasi pada kelompok pasien dengan tingkat sosioekonomi menengah keatas dan kebiasaan merokok dengan hasil tidak terdapat perbedaan bermakna dari OHIS antara pasien DMT2 dan kontrol tanpa DM.…”
Section: Bahasanunclassified